The Mediating Role of Perceived Risk in the Relationship between Restaurant Food Hygiene Quality and Consumer Purchase Intention - Ungku Zainal Abidin, Ungku Fatimah (2007)
As the concern for food safety increases among consumers today, the foodservice industry inevitably has to strive to meet the required food hygiene quality. Previous literatures have widely suggested the significant role of food safety in consumer purchase intention. Yet, theoretical model in understanding how food hygiene influences consumer behavioral intention in purchasing food away from home is lacking. Drawing from the theory of perceived risk, this study empirically examined the mediating effect of perceived risk on the relationship between food hygiene standard of an eating establishment and consumer purchase intention. A survey was conducted on two types of foodservice establishments (i.e. quick service restaurant, QSR and full service restaurant, FSR). A total of 525 adult respondents (260 from QSR and 265 from FSR) were selected following a systematic random purposive sampling procedure. Exploratory factor analysis revealed three underlying factors of food hygiene (i.e. preparation and serving process, staff and handling practices, and food) from consumers' point of view. A model incorporating the three factors was developed using structural equation modeling. The assessment of the overall structural model for FSR and QSR indicated that the effect of food hygiene on consumer perceived risk and purchase intention differed between the two types of foodservice establishments. Results showed that the effect of food hygiene factors on consumer purchase intention differs between FSR and QSR. It is suggested that the menu price paid to dine in an establishment may influence the impact of food hygiene on purchase intention. Consumers are more tolerant and would not expect everything of high standard of hygiene if they were to pay less. On the contrary, consumers anticipate high standard of food hygiene with the relatively high menu price paid. In addition, results showed that the food hygiene factors influence consumer perceived risk in FSR and QSR differently. The perceived risk is expected be affected by the invisibility of food hygiene factors. Consumers tend to be optimistic about the potential risk when food hygiene is not apparent to them. Finally, this study demonstrated that perceived risk is only a partial mediator. From consumers’ point of view food hygiene need not be associated with food safety matters. Consumers are unable to differentiate food hygiene as food safety related factors from those reflect only aesthetics value. Moreover, consumers may not have the right judgment regarding the risk associated with food hygiene.